The potential of carbonate apatite as an alternative bone substitute material (Medical Journal of Indonesia, 2019)
Bone reconstructive surgery has become a common procedure, and bone transplantation has become the second most frequently performed tissue transplantation procedure worldwide. Therefore, the need for bone substitute materials has increased. Artificial bone substitutes exhibit osteoconductive properties and feature several advantages, including abundant resources, low cost, and low donor site morbidity. Carbonate apatite (CO3Ap) is a calcium phosphate ceramic that can be used as a synthetic bone graft. The carbonate content of this ceramic is similar to that of bone apatite. In this review, we show that carbonate apatite can be degraded given its chemical reactivity in a weakly acidic environment and through osteoclast resorption. Moreover, it is osteoconductive and promotes bone tissue formation without fibrotic tissue formation. Additionally, microstructural analysis revealed that new bone tissue is formed within the bone graft itself.